Oxygen Deficit is Related to the Exercise Time to Exhaustion at Maximal Aerobic Speed in Middle Distance Runners - Renoux, J.; Petit, B.; Billat, V.; Koralsztein, J. P. (Archives of Physiology and Biochemistry, 1999)
The purpose of this study was to show the relationship between oxygen deficit and the time to exhaustion (tlim) at maximal aerobic speed (MAS). The minimum speed that elicits VO2max was assumed to be the maximal aerobic speed (MAS). Fourteen subelite male runners (mean (SD: age = 27 ± 5 yrs: VO2max = 68.9 ± 4.6 ml kg -1 .min -1 ; MAS = 21.5 ± 1 km h -1 ) participated in the study. Each subject performed an incremental test to determine and MAS. The subjects ran to exhaustion at velocities corresponding to 100 and 120 % MAS. Oxygen deficit was measured during the period exercise to exhaustion at 120% of MAS and was calculated from the difference between O2 demand and the accumulated O 2 uptake. The tlim values at 100% MAS were correlated with the values of tlim at 120% MAS (r = 0.52). The results reveal that the oxygen deficit was related to the time to e xhaustion at MAS and indicate that the greater the oxygen deficit, the greater the time to exhaustion at MAS. It was also noted that the adjustment of oxygen consumption is related to the oxygen deficit. In other words, the subjects who have an important anaerobic capacity are the most efficient during an exercise time to exhaustion at MAS. The time limit values can beexpressed by a linear regression making intervene MAS and anaerobic capacity. This conclusion could be of great interest in the training of middle distance runners.